Dual band miniaturized microstrip slot antenna for WLAN applications - Ali, Murtaza S.M. (John Wiley and Sons Ltd, 2016)
A miniaturized dual band Microstrip Slot antenna operating at 2.45 GHz and 5.8 GHz is presented. The antenna element consists of a microstrip line-fed metal patch with various slots on the patch resonator. To realize dual band characteristics, a pair of mirror-image L-shaped slots and a pair of slits on the patch resonator are utilized. The square slot in the middle of the patch is etched to enable more compactness, with a 41.2% area reduction as compared to a conventional square patch antenna. The measurement results demonstrate that the proposed antenna provides acceptable radiation performances with directional radiation patterns at desired frequencies.